Strategi Positioning Slank dalam Menanamkan Citra sebagai Salah Satu Grup Band di Indonesia - Reagan, M.Ronald; Rosilawati, Yeni (Jurnal Ilmu Komunikasi, 2009)
Â Abstract: This research is aimed to analyze the positioning strategy of music group band, the Slank, that still now can exist in Indonesia.The Slank is offering some differentiation that can be identified, offering an unique selling proposition (USP) that can be differentiate among their competitors. Some several findings in the research are: the Slank delivers a tagline âpolos dan apa adanyaâ (means innocent and just be yourself) which contains solid and clear messages to their audience. This message divulged in their overall activities including in how they communicate and promote to their audience. The message âpolos dan apa adanyaâ have been emerging in various of a medium that Slank used to communicate, including music and the lyrics of the songs, video clips, their performances or life style in their daily activities, their cover and logo, Slankâs live show and Slankâs merchandises. From their lyrics of the Slank song titled Seperti Para Koruptor, the Slank gives a clear message to persuade the audiences to live with humble and just be ourselves because in the living world, happiness and peaceful is much more worthed instead of being rich and famous. With all that efforts, the Slank tries to place their image among their audience and trying to be unique and different. Positioning strategy that pertain to the Slank should be managed and controlled in order to surviving Slank among of the competitors.